Quality of life endpoints in cancer cachexia clinical trials: Systematic review 3 of the cachexia endpoints series - Marianne J. Hjermstad; Gunnhild Jakobsen; Jann Arends; Trude R. Balstad; Leo R. Brown; Asta Bye; Andrew J.S. Coats; Olav F. Dajani; Ross D. Dolan; Marie T. Fallon; Christine Greil; Alexandra Grzyb; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2024)
Abstract The use of patient‐reported outcomes (PROMs) of quality of life (QOL) is common in cachexia trials. Patients' self‐report on health, functioning, wellbeing, and perceptions of care, represent important measures of efficacy. This review describes the frequency, variety, and reporting of QOL endpoints used in cancer cachexia clinical trials. Electronic literature searches were performed in Medline, Embase, and Cochrane (1990–2023). Seven thousand four hundred thirty‐five papers were retained for evaluation. Eligibility criteria included QOL as a study endpoint using validated measures, controlled design, adults (>18 years), ≥40 participants randomized, and intervention exceeding 2 weeks. The Covidence software was used for review procedures and data extractions. Four independent authors screened all records for consensus. Papers were screened by titles and abstracts, prior to full‐text reading. PRISMA guidance for systematic reviews was followed. The protocol was prospectively registered via PROSPERO (CRD42022276710). Fifty papers focused on QOL. Twenty‐four (48%) were double‐blind randomized controlled trials. Sample sizes varied considerably (n = 42 to 469). Thirty‐nine trials (78%) included multiple cancer types. Twenty‐seven trials (54%) featured multimodal interventions with various drugs and dietary supplements, 11 (22%) used nutritional interventions alone and 12 (24%) used a single pharmacological intervention only. The median duration of the interventions was 12 weeks (4–96). The most frequent QOL measure was the EORTC QLQ‐C30 (60%), followed by different FACIT questionnaires (34%). QOL was a primary, secondary, or exploratory endpoint in 15, 31 and 4 trials respectively, being the single primary in six. Statistically significant results on one or more QOL items favouring the intervention group were found in 18 trials. Eleven of these used a complete multidimensional measure. Adjustments for multiple testing when using multicomponent QOL measures were not reported. Nine trials (18%) defined a statistically or clinically significant difference for QOL, five with QOL as a primary outcome, and four with QOL as a secondary outcome. Correlation statistics with other study outcomes were rarely performed. PROMs including QOL are important endpoints in cachexia trials. We recommend using well‐validated QOL measures, including cachexia‐specific items such as weight history, appetite loss, and nutritional intake. Appropriate statistical methods with definitions of clinical significance, adjustment for multiple testing and few co‐primary endpoints are encouraged, as is an understanding of how interventions may relate to changes in QOL endpoints. A strategic and scientific‐based approach to PROM research in cachexia trials is warranted, to improve the research base in this field and avoid the use of QOL as supplementary measures.